Development of the breastfed infant oral microbiome over the first two years of life in the BLOSOM Cohort - Roaa A. Arishi; Roaa A. Arishi; Roaa A. Arishi; Roaa A. Arishi; Ali S. Cheema; Ching T. Lai; Ching T. Lai; Ching T. Lai; Matthew S. Payne; Donna T. Geddes; Donna T. Geddes; Donna T. Geddes; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundAcquisition and development of the oral microbiome are dynamic processes that occur over early life. This study aimed to characterize the temporal development of the oral microbiome of predominantly breastfed infants during the first two years of life.MethodsInfant oral samples (n=667) were collected at ten time points from the first week to year two of life from 84 infants. Bacterial DNA profiles were analyzed using full-length 16S rRNA gene sequencing.ResultsThe oral microbiome was dominated by Streptococcus mitis, Gemella haemolysans, and Rothia mucilaginosa. Bacterial richness decreased from 1 to 2 months (P = 0.043) and increased from 12 to 24 months (P = 0.038). Shannon diversity increased from 1 week to 1 month and again from 6 to 9 months and 9 to 12 months (all P ≤ 0.04). The composition of the infant oral microbiome was associated with multiple factors, including early pacifier use, intrapartum antibiotic prophylaxis, maternal allergy, pre-pregnancy body mass index, siblings, delivery mode, maternal age, pets at home, and birth season (all P < 0.01). Introduction of solid foods was a significant milestone in oral microbiome development, triggering an increase in bacterial diversity (richness P = 0.0004; Shannon diversity P = 0.0007), a shift in the abundance of seven species, and a change in beta diversity (P = 0.001).ConclusionThese findings underscore the importance of multiple factors, particularly the introduction of solid foods, in shaping the oral microbiome of breastfed infants during early life.